Regime Type and COVID-19 Response. Issue 3 (September 2020) - Alon, Ilan; Farrell, Matthew; Li, Shaomin
From late 2019 to the first half of 2020, the world has witnessed the epic spread and destruction of the novel coronavirus which was discovered in Wuhan, China. The huge number of infections and deaths caused by the virus, the collapse of the healthcare system and the economic consequences have few modern equivalents. While governments of all countries are responding to the pandemic, a heated debate rages about which political system, democracy versus authoritarian, is better positioned to respond to the pandemic. While the worldwide effort to contain the virus continues, we offer a preliminary comparison between democracies and authoritarian regimes in their responses to COVID-19, and policy suggestions for democracies to improve their governance and their ability to respond to crises.